Slavistična prepletanja 2 (University of Maribor Press, 2022)
The scientific monograph Slavic Intertwining 2 includes seventeen papers in the field of research into Slavic literature and translation contacts between Slavic languages, as well as interdisciplinary research into Slavic literature. The monograph opens with a set of contributions that deal with Slavic literature through the prism of interculturality, while the translations of Slavic literature as cultural transfers are the focus of the contributions of the second set. The third part of the monograph focuses on research into older periods of Slavic literature, and the monograph is closed by contributions from the field of literary and artistic intermediality and film adaptations of Slavic literature. Intercultural and translation research of Slavic literature, research of older periods of Slavic literature and adaptations of Slavic literature are just some of the research challenges of Slavic literary research, which are relevant both in terms of research topics and methodologies.